On the weak impact of base money on broad money in the context of unconventional monetary policy: Euro Area 2008-2024 - Carlos Pateiro-Rodríguez; Federico Martín-Bermúdez; Esther Barros-Campello; Carlos Pateiro-López (Economies, 2025)
In its response to the economic and financial crises of 2008, the sovereign debt and euro crisis of 2010-2015, and the COVID-19 pandemic of 2020-2023, the European Central Bank (ECB) implemented an unconventional monetary policy aimed at providing liquidity for more than a decade, through a complex set of tools and operations that make up the so-called quantitative easing. The results of all of them are being analyzed from different perspectives. This paper studies the relationship between a large base money, characterized by a voluminous concentration of liquidity in the form of excess reserves, and broad money (the broad M3 aggregate). Our econometric work shows a low elasticity of broad money with respect to base money, concluding the existence of a weak relationship between both monetary magnitudes, with a sharp decline in the money multiplier. The demand for money has remained stable relative to its determining variables, interest rates and income. At the same time, some practices related to the handling of excess liquidity by European banks through deposit facilities deserve consideration. We propose strict control by the monetary authority over the nature and origin of the funds that constitute the excess liquidity derived from the ECB's unconventional operations, and over its management.
Keywords: 330; quantitative easing; base money; broad money; deposit facility; central bank